#### Answer

-$\frac{3}{4z}$

#### Work Step by Step

$\frac{3}{16z}$ - $\frac{15}{16z}$
= $\frac{3-15}{16z}$
=$\frac{-12}{16z}$
=-$\frac{4\times 3}{4\times4z}$
=-$\frac{3}{4z}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-$\frac{3}{4z}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.